Pediatric Blood Pressure and Cardiovascular Health in Adulthood - Meng, Yaxing; Mynard, Jonathan P.; Smith, Kylie J.; Juonala, Markus; Urbina, Elaine M.; Niiranen, Teemu; Daniels, Stephen R.; Xi, Bo; Magnussen, Costan G. (Springer Nature, 2025)
Purpose of review: This review summarizes current knowledge on blood pressure in children and adolescents (youth), with a focus on primary hypertension-the most common form of elevated blood pressure in this demographic. We examine its etiology, progression, and long-term cardiovascular implications. The review covers definitions and recommendations of blood pressure classifications, recent developments in measurement, epidemiological trends, findings from observational and clinical studies, and prevention and treatment, while identifying gaps in understanding and suggesting future research directions.
Recent findings: Youth hypertension is an escalating global issue, with regional and national variations in prevalence. While the principles of blood pressure measurement have remained largely consistent, challenges in this age group include a scarcity of automated devices that have passed independent validation for accuracy and a generally limited tolerance for ambulatory blood pressure monitoring. A multifaceted interplay of factors contributes to youth hypertension, impacting long-term cardiovascular health. Recent studies, including meta-analysis and sophisticated life-course modelling, reveal an adverse link between youth and life-course blood pressure and subclinical cardiovascular outcomes later in life. New evidence now provides the strongest evidence yet linking youth blood pressure with clinical cardiovascular events in adulthood. Some clinical trials have expanded our understanding of the safety and efficacy of antihypertensive medications in youth, but this remains an area that requires additional attention, particularly regarding varied screening approaches. This review outlines the potential role of preventing and managing blood pressure in youth to reduce future cardiovascular risk. A global perspective is necessary in formulating blood pressure definitions and strategies, considering the specific needs and circumstances in low- and middle-income countries compared to high-income countries.